An Exploration of the Nexus Between Inner and Outer Sustainability - Cooper, Kira Jade (University of Waterloo, 2023)
As sustainability challenges intensify, there is increasing interest in exploring how changes in individual mindsets can support positive transformations at scale. Researchers at the interface of inner and outer sustainability now need to understand how approaches to inner transformation may support or undermine conditions for long-term wellbeing. The purpose of this dissertation is to advance understanding of how inner and outer sustainability might be enhanced in a mutually supportive manner. Drawing on insights from an integrative literature review, a hybridized inner-outer sustainability assessment framework was developed to inform assessment of whether and how approaches to inner transformations might contribute to collective wellbeing. Application of the framework was then illustrated and tested in a case study assessing the sustainability contributions and limitations of three mindfulness-based events that took place at the onset of the COVID-19 pandemic. Findings from the analysis revealed considerable promise for inner transformation approaches to support skills and competencies such as empathy and compassion that are needed to foster more sustainable mindsets and practices. The case study analysis also found that many requirements for outer sustainability were overlooked in the interventions and that inner transformations, if approached from the perspective of individual development and wellness, can worsen conditions for collective flourishing. Results of the case study analysis inform how approaches to inner and outer sustainability might be contextualized anew to enhance synergies between the inner and outer dimensions and reduce potential trade-offs. Lastly, the study explored emerging themes and opportunities future research in this novel field of study. Outcomes of the research should inform future interventions for inner transformation as well as conventional approaches to sustainability assessment practices. While the case study analysis focused largely on mindfulness-based offerings, the results are of relevance to systemic transformations more broadly.
Keywords: sustainability; inner transformation; mindfulness